2018
DOI: 10.1177/1933719117697127
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming: Gestational Exposure to Excess Testosterone Alters Expression of Ovarian Matrix Metalloproteases and Their Target Proteins

Abstract: Prenatal testosterone (T)-treated sheep, similar to women with polycystic ovary syndrome (PCOS), manifests reproductive defects that include multifollicular ovarian phenotype. Women with PCOS manifest increased ovarian matrix metalloproteinases (MMPs) activity. We tested the hypothesis that gestational T excess in sheep would alter ovarian expression of MMPs, tissue inhibitors of MMP (TIMP) and their target proteins laminin B (LAMB), collagen, tumor necrosis factor alpha (TNF), and connexin 43 (GJA1) consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Intrauterine programming has been proposed as one of the plausible mechanisms that cause PCOS, as evidenced by the high heritability of the disease and animal models demonstrating that prenatal exposure to high levels of androgens or AMH results in the acquisition of the PCOS phenotype in the offspring (Filippou & Homburg 2017, Tata et al 2018. To date, several studies have been conducted in prenatal androgenized sheep and monkeys in which a PCOS phenotype was observed during adulthood, which, in turn, has been related to DNA methylation changes in the case of monkeys (Manikkam et al 2006, Abbott et al 2008, Veiga-Lopez et al 2008, 2012, Smith et al 2009, Ortega et al 2010, Xu et al 2011, Padmanabhan et al 2014, Puttabyatappa et al 2018. Nevertheless, little…”
Section: Dna Methylation In the Peripheral And Cord Blood From Women mentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine programming has been proposed as one of the plausible mechanisms that cause PCOS, as evidenced by the high heritability of the disease and animal models demonstrating that prenatal exposure to high levels of androgens or AMH results in the acquisition of the PCOS phenotype in the offspring (Filippou & Homburg 2017, Tata et al 2018. To date, several studies have been conducted in prenatal androgenized sheep and monkeys in which a PCOS phenotype was observed during adulthood, which, in turn, has been related to DNA methylation changes in the case of monkeys (Manikkam et al 2006, Abbott et al 2008, Veiga-Lopez et al 2008, 2012, Smith et al 2009, Ortega et al 2010, Xu et al 2011, Padmanabhan et al 2014, Puttabyatappa et al 2018. Nevertheless, little…”
Section: Dna Methylation In the Peripheral And Cord Blood From Women mentioning
confidence: 99%
“…These molecular and morphological changes in the ovarian tissue could be attributed to epigenetic alterations as proposed in animal models of PCOS. Predominantly, studies have reported that prenatal testosterone treatment in sheep results in an increase in the occurrence of persistent and growing follicles (contributing to the morphology of a PCO), luteal and antral follicles defects, a decline in primordial follicles and an altered ovarian protein content of AMH, ovarian steroidogenic enzymes, matrix metalloproteases and proteins related to insulin pathway during adulthood (Manikkam et al 2006, Veiga-Lopez et al 2008, 2012, Smith et al 2009, Ortega et al 2010, Padmanabhan et al 2014, Puttabyatappa et al 2018. Remarkably, this fetal programming induced by prenatal testosterone correlates with defects in the expression of ovarian steroidogenic genes and miRNAs associated with insulin pathway in the ovaries of fetal ewes (Luense et al 2011).…”
Section: Dna Methylation In the Ovarian Tissue And Granulosa Cells Frmentioning
confidence: 99%
“…The MMP family belongs to zinc‐ and calcium‐dependent metalloproteinases and encompasses at least 28 members that can be subdivided into four broad classes: collagenases, gelatinases, stromelysins, and membrane‐type MMPs . Several members of the MMP family (e.g., MMP1, MMP2, MMP7, MMP9, and MMP13) are expressed in mammalian ovarian follicles at different developmental stages, and the expression of these MMPs is highly regulated in response to gonadotropins, sex hormones, and growth factors . For instance, MMP1 and MMP9 are expressed in granulosa cells at all follicular stages, and MMP2 is expressed in the granulosa/cumulus cells of early and antral follicles .…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of cows that were in estrus was higher for cows that received two PG {EPG-PG} than for cows that received one PG {ECO-72} in this study. Luteolysis was greater for two PG injections compared to a single PG injection (Ribeiro et al, 2012). The two injections of PG on days 5 and 6 after the first GnRH were needed to maximize the percentage of cows that underwent complete CL regression be-fore TAI.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing the follicular dominance by as few as 1.5 d can compromise embryonic survival (Cerri et al, 2009). This idea was used by Santos et al (2010) and Ribeiro et al (2012) to shift back the PG from day 7 to day 5 and to add another dose on day 6 in the Cosynch 72 protocol to avoid the problem of incomplete regression of CL, particularly in presynchronized cows which have a high ovulation rate in response to the first GnRH. The results of both studies indicated an overall improvement in fertility, including lower P4 concentrations and higher CL regression at TAI, a smaller diameter of the ovulatory follicle, higher P /AI and the tendency for an increasing synchronization rate for cows that received two PG injections on days 5 and 6 of the Cosynch 72 protocol.…”
Section: Introductionmentioning
confidence: 99%